A mechanics-based perspective on the pressure-cross-sectional area loop within the esophageal body - Elisha, Guy; Halder, Sourav; Carlson, Dustin A.; Kahrilas, Peter J.; Pandolfino, John E.; Patankar, Neelesh A. (Frontiers in Physiology, 2023)
Plotting the pressure-cross-sectional area (P-CSA) hysteresis loops within the esophagus during a contraction cycle can provide mechanistic insights into esophageal motor function. Pressure and CSA during secondary peristalsis can be obtained from the functional lumen imaging probe (FLIP). The P- CSA plots at a location within the esophageal body (but away from the sphincter) reveal a horizontal loop shape. The horizontal loop shape has phases that appear similar to those in cardiovascular analysis, which include isometric and isotonic contractions followed by isometric and isotonic relaxations. The aim of this study is to explain the various phases of the P-CSA hysteresis loop within the esophagus body. To that end, we simulate flow inside a FLIP device placed inside the esophagus lumen. We focus on three scenarios: long FLIP bag placed inside the esophagus but not passing through the lower esophageal sphincter (LES), long FLIP bag that crosses the LES, and a short FLIP bag placed in the esophagus body that does not pass through the LES. The results show that the horizontal P-CSA loop pattern is robust and is reproduced in all three cases with only small differences. Results indicate that the horizontal loop pattern is primarily a product of mechanical conditions rather than any inherently different function of the muscle itself. Thus, the distinct phases of the loop can be explained solely based on mechanics.